Paysage, médiation paysagère et « bon état écologique » de la haute vallée de la Sèvre niortaise - Rémi Bercovitz (Projets de Paysage)
All water policies oscillate among several preoccupations and mobilize a wide variety of actors with sometimes contradictory interests. The running conflict surrounding valley landscapes is today being reorganized around a new goal : assuring that watercourses reach a “good ecological status.” It is within this context of rearrangement of action intentionality that our research, approaching the landscape as both an object of knowledge and a decision-making tool, lies. We indeed postulate that given the diversity of the social expectations deciders are obliged to deal with, it is important to be able to refer to an integrating framework of reflection and action. For me the landscape constitutes just such a framework and is thus envisaged as being a tool of mediation facilitating the emergence of a new “socio-territorial contract.” On the basis of this hypothesis, we present the methodological foundations of a procedure which, applied to the case of the Sevre Niortaise valley landscapes, relies on the construction and sharing of historical knowledge.